Combined analysis of lipidomics and transcriptomics revealed the key pathways and genes of lipids in light-sensitive albino tea plant (Camellia sinensis cv. Baijiguan) - Zhou, Zhe; Chen, Mingjie; Wu, Quanjin; Zeng, Wen; Chen, Zhidan; Sun, Weijiang (Frontiers in Plant Science, 2022)
Currently, the mechanism by which light-sensitive albino tea plants respond to light to regulate pigment synthesis has been only partially elucidated. However, few studies have focused on the role of lipid metabolism in the whitening of tea leaves. Therefore, in our study, the leaves of the Baijiguan (BJG) tea tree under shade and light restoration conditions were analyzed by a combination of lipidomics and transcriptomics. The leaf color of BJG was regulated by light intensity and responded to light changes in light by altering the contents and proportions of lipids. According to the correlation analysis, we found three key lipid components that were significantly associated with the chlorophyll SPAD value, namely, MGDG (36:6), DGDG (36:6) and DGDG (34:3). Further weighted gene coexpression network analysis (WGCNA) showed that HY5 TF and GLIP genes may be hub genes involved lipid regulation in albino tea leaves. Our results lay a foundation for further exploration of the color changes in albino tea leaves.